Formation and development of the noospheric vector in the educational paradigm of the 21st century - Punchenko, Oleg P.; Vodopianov, Pavel A. (Journal of the Belarusian State University. Sociology, 2024)
The noospheric vector in the development of the modern education system is investigated. Its deterministic basic components are described, the key among which is the informatisation of education through the introduction of intelligent information technologies. The expediency of ensuring the humanisation and humanitarisation of education as necessary conditions for preserving the unity of the scientific knowledge system is analysed. The influence of innovations on the learning process is shown. Special attention is paid to the noosphere-information paradigm of education, which is a complex of scientific, technical and socio-ideological innovations involving the use of intelligent information technologies in education. The necessity of approving the ideas of the new Enlightenment aimed at achieving a secure future is substantiated.
Keywords: education; informatisation; humanitarisation; humanity; innovation